HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR SISWA PADA PEMBELAJARAN BIOLOGI DI KELAS XI SMA TRI BHAKTI PEKANBARU - Devitriana '; Arnentis '; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study is for the purpose of this study is to determine whether or not the relationship between motivation with student learning outcomes on biology learning in the class XI SMA Tri Bhakti Pekanbaru . This research was conducted from August to October 2016. The sample in this study were 39 students of class XI SMA Tri Bhakti Pekanbaru. The instruments of data collection used are closed questionnaire, student attitude observation sheet and product assessment sheet. Closed Questionnaire with 30 statements consisting of 9 indicators of desire and desire, encouragement and learning needs, future expectations and aspirations, interests, awards in learning, exciting activities in learning, a conducive learning environment, competition , And punishment. All closed questionnaire items are valid and reliable. Closed questionnaires of student learning motivation are tested by correct item total correlation method, where all statement items are declared valid. To test the reliability of questionnaire through Cronbach's alpha test obtained alpha of 0.917. This validity and reliability test is analyzed with SPSS (Statistical Package for Social Studies) version 17.00 for Windows. The collected data were analyzed descriptively. The relationship of motivation with student learning outcomes in the biology learning in the class XI SMA Tri Bhakti Pekanbaru obtained as follows: Motivation with students' cognitive learning results showed the correlation coefficient (rarithmetic) of 0.630 with strong category, motivation with student affective learning results show correlation coefficient (rarithmetic) Equal to 0,561 with medium category, and motivation with student psychomotor result show correlation coefficient (rarithmetic) equal to 0,373 with weak category. The relationship of motivation with students' learning outcomes was significantly positive with a significance level of 5% (0.325). Then any increase in score/value of motivation score will be followed by increase score / value of student learning outcomes.Keywords: Relationship, Motivation, Learning Result